2003
DOI: 10.1073/pnas.1635049100
|View full text |Cite
|
Sign up to set email alerts
|

Fruit odor discrimination and sympatric host race formation in Rhagoletis

Abstract: Rhagoletis pomonella is a model for incipient sympatric speciation (divergence without geographic isolation) by host-plant shifts. Here, we show that historically derived apple-and ancestral hawthorn-infesting host races of the fly use fruit odor as a key olfactory cue to help distinguish between their respective plants. In flight-tunnel assays and field tests, apple and hawthorn flies preferentially oriented to, and were captured with, chemical blends of their natal fruit volatiles. Because R. pomonella rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
296
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(314 citation statements)
references
References 30 publications
14
296
0
1
Order By: Relevance
“…The phytochemical mediation of sexual communication, including rendezvous cues (IV-2) in conjunction with host recognition (I-1, I-2), may be of great importance particularly at the initial stage of speciation, although such a process has not been well understood. 75,79) On another front, phytochemical cues and their derivatives also provide us with innovative tools for pest management. However, in the case of fruit fly attractants, such as the synomones mediating orchid-fruit fly interactions, the intensive use of such allelochemicals in RK-sensitive RK-sensitive ME-sensitive + Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phytochemical mediation of sexual communication, including rendezvous cues (IV-2) in conjunction with host recognition (I-1, I-2), may be of great importance particularly at the initial stage of speciation, although such a process has not been well understood. 75,79) On another front, phytochemical cues and their derivatives also provide us with innovative tools for pest management. However, in the case of fruit fly attractants, such as the synomones mediating orchid-fruit fly interactions, the intensive use of such allelochemicals in RK-sensitive RK-sensitive ME-sensitive + Fig.…”
Section: Resultsmentioning
confidence: 99%
“…79) Divergence of incipient populations and speciation in phytophagous insects may be driven by such hostrelated chemical cues, both in habitat-specific mating choice and in host preference by ovipositing females, although this warrants further in-depth investigations.…”
Section: Plant Signals For Rendezvous Cuesmentioning
confidence: 99%
“…Changes in specificity are more common than alterations to plant ranking ( Jaenike, 1990;Funk & Bernays, 2001 ). Both can evolve rapidly ( Thomas et al , 1987;Singer et al , 1993 ) and can differ even between sympatric populations ( Prokopy et al , 1988;Craig et al , 1993;Via, 1999 ;Linn et al , 2003), yet species sometimes show conserved preferences ( Thompson, 1993;Wehling & Thompson, 1997 ). Several explanations have been proposed for conservatism ( Thompson, 1993;Wehling & Thompson, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that that volatiles emitted from the surface of ripening fruit are important long-and short-range chemosensory cues used to discriminate among potential host plants (Frey and Bush, 1990). More specifically, it was shown that, in both field and wind-tunnel experiments, apple flies are more attracted to volatile chemicals that are typical of apples than they are to those of hawthorn fruit (Linn et al, 2003). Hawthorn flies and the closely related flowering dogwood fly, Rhagoletis sp.…”
Section: Caribbean/ Africa Rest_of_the_worldmentioning
confidence: 99%